EXPOSURE EFFECT OF MAGNETIC FIELD ON WATER PROPERTIES IN RECIRCULATION AQUACULTURE SYSTEMS(RAS) - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study to investigate the effect of magnetic field on water properties recirculatingaquaculture systems. This study is based on previous works reporting the positive effects of exposureto magnetic field on water properties, plant growth, plant germination, livestock-drinking water, andfish fertilisation. It was conducted against the backdrop of serious issues pertaining to water quality inrecirculating aquaculture systems, which negatively impact aquaculture species growth. First, thiswork evaluates the effect of exposed to magnetic field intensities of 0.10, 0.15, 0.20, 0.10+0.15,0.10+0.20, 0.15+0.20, and 0.10+0.15+0.20 T on water quality. The results showed significant (p < 0.05)increases of the dissolved oxygen (DO), pH, and conductivity(CD) by 17.3, 1.6, 3.0%, respectively, andsignificant decreases of the ammonium level(NH4-N), specific conductivity(SPC), total dissolvedsolids(TDS), oxygen reduction potential(ORP), and chlorides by 25.3, 1.1, 1.4, 1.0, 16.9, 3.4%,respectively, throughout the experiment in recirculation aquaculture systems. Therefore, theinstallation of the device in recirculation aquaculture systems is simple, low cost, and can be retrofittedinto existing systems, which helps simplify fish rearing for fish farmers.